Application of targeted diagnosis of PSMA in the modality shift of prostate cancer diagnosis: a review - Yan, Li; Zhang, Zhengchao; Wang, Ting; Yuan, Leihong; Sun, Xiaoke; Su, Pengxiao (Frontiers in Oncology, 2023)
Prostate cancer (PCa) is a serious threat to the health of men all over the world. The progression of PCa varies greatly among different individuals. In clinical practice, some patients often progress to advanced PCa. Therefore, accurate imaging for diagnosis and staging of PCa is particularly important for clinical management of patients. Conventional imaging examinations such as MRI and CT cannot accurately diagnose the pathological stages of advanced PCa, especially metastatic lymph node (LN) stages. As a result, developing an accurate molecular targeted diagnosis is crucial for advanced PCa. Prostate specific membrane antigen (PSMA) is of great value in the diagnosis of PCa because of its specific expression in PCa. At present, researchers have developed positron emission tomography (PET) targeting PSMA. A large number of studies have confirmed that it not only has a higher tumor detection rate, but also has a higher diagnostic efficacy in the pathological stage of advanced PCa compared with traditional imaging methods. This review summarizes recent studies on PSMA targeted PET in PCa diagnosis, analyzes its value in PCa diagnosis in detail, and provides new ideas for urological clinicians in PCa diagnosis and clinical management.